2014
DOI: 10.1287/mnsc.2013.1784
|View full text |Cite
|
Sign up to set email alerts
|

Holding the Hunger Games Hostage at the Gym: An Evaluation of Temptation Bundling

Abstract: We introduce and evaluate the effectiveness of temptation bundling—a method for simultaneously tackling two types of self-control problems by harnessing consumption complementarities. We describe a field experiment measuring the impact of bundling instantly gratifying but guilt-inducing “want” experiences (enjoying page-turner audiobooks) with valuable “should” behaviors providing delayed rewards (exercising). We explore whether such bundles increase should behaviors and whether people would pay to create thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 229 publications
(67 citation statements)
references
References 57 publications
1
59
0
Order By: Relevance
“…Limiting access to want options (e.g., installing antiprocrastination software) may also help keep long-term goals salient via managing the personal environment of the media user (Ariely & Wertenbroch, 2002). Finally, people might also benefit from pairing shortterm hedonic pleasures with long-term goals, for example by listening to music while studying or by only allowing oneself to indulge in want choices while at the gym (Milkman, Minson, & Volpp, 2014;Wang & Tchernev, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Limiting access to want options (e.g., installing antiprocrastination software) may also help keep long-term goals salient via managing the personal environment of the media user (Ariely & Wertenbroch, 2002). Finally, people might also benefit from pairing shortterm hedonic pleasures with long-term goals, for example by listening to music while studying or by only allowing oneself to indulge in want choices while at the gym (Milkman, Minson, & Volpp, 2014;Wang & Tchernev, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Sophisticated individuals can, and often do, take steps to overcome limited self-control. Anticipating that they may not follow through on their intentions, they value and adopt commitment devices, which increase the future costs of failing to follow through (e.g., taking the medication Antabuse in the morning to induce vomiting if alcohol is consumed later in the day; Ashraf, Karlan, & Yin, 2006; Milkman, Minson, & Volpp, 2014; Rogers, Milkman, & Volpp, 2014; Schwartz et al, 2014). …”
Section: Follow-through Failuresmentioning
confidence: 99%
“…In addition, Milkman et al suggested a method of "temptation bundling" to overcome self-control problems. 90 Specifically, in a field experiment, they found that individuals who used "low brow" audiobooks at the gym (ie, a source of immediate gratification) significantly increased their attendance at the fitness center compared with control group participants who did not use audiobooks. 72,90 Thus, this strategy could be suggested to patients to increase adherence to their physical activity plan.…”
Section: Strategies For Dealing With Present Time Bias In the Clinicamentioning
confidence: 99%